Psychological mechanisms and functions of 5-HT and SSRIs in potential therapeutic change: Lessons from the serotonergic modulation of action selection, learning, affect, and social cognition. (December 2020) - Roberts, Clark; Sahakian, Barbara J.; Robbins, Trevor W.
Highlights: Laboratory paradigms with serotonergic manipulations indicate several context and trait-specific effects which possibly relate to variability seen in SSRI effects. 5-HT neurons adaptively assist in coding for stress, surprise, and valence shifts to resolve uncertainty and motivational trade-offs, as well as enhancing behavioural flexibility. Specific direct effects of 5-HT transmission in rewarding or aversive contexts are mediated by receptor sub-type morphology and semi-flexible circuits which are under both genetic and developmental control. Predicting individual-level treatment outcomes may require a broader idiographic analysis of the dynamics of goal-directed behaviour. 5-HT has distinctive effects in modulating prosocial cognition, paralleling behaviours seen in non-social paradigms. Abstract: Uncertainty regarding which psychological mechanisms are fundamental in mediating SSRI treatment outcomes and wide-ranging variability in their efficacy has raised more questions than it has solved. Since subjective mood states are an abstract scientific construct, only available through self-report in humans, and likely involving input from multiple top-down and bottom-up signals, it has been difficult to model at what level SSRIs interact with this process. Converging translational evidence indicates a role for serotonin in modulating context-dependent parameters of action selection, affect, and social cognition; and concurrently supporting learning mechanisms, which promote adaptability and behavioural flexibility. We examine the theoretical basis, ecological validity, and interaction of these constructs and how they may or may not exert a clinical benefit. Specifically, we bridge crucial gaps between disparate lines of research, particularly findings from animal models and human clinical trials, which often seem to present irreconcilable differences. In determining how SSRIs exert their effects, our approach examines the endogenous functions of 5-HT neurons, how 5-HT manipulations affect behaviour in different contexts, and how their therapeutic effects may be exerted in humans – which may illuminate issues of translational models, hierarchical mechanisms, idiographic variables, and social cognition.